2023
DOI: 10.21121/eab.1101907
|View full text |Cite
|
Sign up to set email alerts
|

Brand Foreignness and Anger Decrease Purchase Intentions of Ethnocentric Consumer for National Icon Products

Abstract: The marketing literature lacks a thorough understanding of how emotions change purchase intentions of ethnocentric consumers' when there are two different nationality signals about the product evaluated (i.e., product nationality signal vs brand nationality signal). To address this gap, we focus on how ethnocentric consumers' purchase intentions for national icon products (product nationality signal) change due to emotional states. Drawing on signaling theory, social identity theory, and the psychology literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…A study conducted by Chan and Lau in 2000 in two major cities of China examined the impact of environmental knowledge on both intention and actual behavior of "green purchasing", and the study revealed that environmental knowledge has a one-to-one effect on purchasing behavior (Yılmaz, 2003). Yılmaz (2013) conducted a study that concluded a significant difference existed in attitudes towards friendly product awareness. According to "B2B Content Marketing 2018: Benchmarks, Budgets, and Trends -North America," published and shared by the Content Marketing Institute, the overall increase in success of the companies surveyed contributed to the following factors;…”
Section: Similar Studies In the Fieldmentioning
confidence: 99%
“…A study conducted by Chan and Lau in 2000 in two major cities of China examined the impact of environmental knowledge on both intention and actual behavior of "green purchasing", and the study revealed that environmental knowledge has a one-to-one effect on purchasing behavior (Yılmaz, 2003). Yılmaz (2013) conducted a study that concluded a significant difference existed in attitudes towards friendly product awareness. According to "B2B Content Marketing 2018: Benchmarks, Budgets, and Trends -North America," published and shared by the Content Marketing Institute, the overall increase in success of the companies surveyed contributed to the following factors;…”
Section: Similar Studies In the Fieldmentioning
confidence: 99%